The freeters spectrum among youth in Malaysia / Siti A’isyah Nabilah Sheikh Ahmad Nasir - Sheikh Ahmad Nasir, Siti A’isyah Nabilah (Faculty of Business and Management, 2019)
This research is conducted to determine the freeters spectrum among youths in Malaysia, and to find out the most influence factors that affect the youth to become freeters. The study was conducted by using the total of 316 respondents all over Malaysia which is focussing on the youth generation. Freeters is one of the common terms that being used in Japan to describe unemployment among graduates at the young age. The questionnaire is being distributed by using online survey which is google form to reach all the respondent in every state in Malaysia. Based on the finding it shows that only lifestyle and preference and unclear ambition for future have a relationship with the freeters spectrum among youth in Malaysia. While lack of self-competence has no relationship with the dependent variables. This study is conducted for about 4 weeks and the findings of the study will be explained further.